The Development of Extra-Articular Manifestations in Children With Enthesitis-Related Arthritis: Natural Course or Different Disease Entity? - Pagnini, Ilaria; Scavone, Mariangela; Maccora, Ilaria; Mastrolia, Maria Vincenza; Marrani, Edoardo; Bertini, Federico; Lamot, Lovro; Simonini, Gabriele (Frontiers in Medicine, 2021)
Introduction: Enthesitis-related Arthritis (ERA) is a specific category of juvenile idiopathic arthritis (JIA) characterized by axial and/or peripheral arthritis, and enthesitis, although other different extra-articular manifestations may encompass its clinical spectrum. Materials and Methods: In order to examine if ERA-JIA with extra-articular involvement may represent a different entity from ERA without extra-articular involvement, we performed a retrospective, observational, monocentric study, in a cohort of ERA patients followed between 2001 and September 2020 at the Pediatric Rheumatology Unit of Meyer Children Hospital of Florence. We analyzed the demographic, clinical, laboratory and imaging data at the disease onset, as well as after 3, 6, and 12 months follow up. Results: We have enrolled 53 patients, 33 males. At the time of diagnosis, average age was 10.9 years, 53 patients had active arthritis and 25 active enthesitis. The middle foot involvement was present in 20 patients. Twenty-five children achieved clinical remission on medication. Extra-articular manifestations were observed in 14 patients, of whom 3 had inflammatory bowel disease, 5 uveitis, one uveitis associated with Crohn disease, 4 SAPHO syndrome, one celiac disease. The cohort was stratified according to the presence/absence of extra-articular manifestations. It was observed that middle foot involvement was more frequent in patients with no extra-articular manifestations (18/39 vs. 2/14; χ2 = 4.45, p = 0.05). Additionally, patients presenting extra-articular manifestation needed more frequently (12/14 vs. 21/39, χ2= 4.45, p = 0.05), and preciously (months: 3.7 ± 5.4 vs. 16.7 ± 26.5, p = 0.02), treatment with biologic agents. Finally, these patients achieved belatedly (months: 31.6 ± 32.3 vs. 22.9 ± 18.3, p = 0.01) and less frequently (3/14 vs. 22/39; χ2= 5.50, p = 0.03) the clinical remission on medication. Eventually, extra-articular involvement inversely correlated with the middle-foot arthritis (ρs −0.29, p = 0.03), the chance to achieve remission on medication (ρs −0.31 e p = 0.02), as well as the chance to keep overall remission, with and without medication (ρs −0.28, p = 0.04). Conclusion: In our cohort, children diagnosed with ERA-JIA at the onset of disease and then developed extra-articular manifestations show the absence of middle foot involvement and worse prognosis with an early need for the use of biologic agents, and overall low chance to achieve remission.